What Drives Oil Prices? Emerging Versus Developed Economies - Knut Are Aastveit; Hilde C. Bjørnland; Leif Anders Thorsrud (Norges Bank, 2012)
We analyze the importance of demand from emerging and developed economies as drivers of the real price of oil over the last two decades. Using a factor-augmented vector autoregressive (FAVAR) model that allows us to distinguish between different groups of countries, we find that demand from emerging economies (most notably from Asian countries) is more than twice as important as demand from developed countries in accounting for the fluctuations in the real price of oil and in oil production. Furthermore, we find that different geographical regions respond differently to oil supply shocks and oilspecific demand shocks that drive up oil prices, with Europe and North America being more negatively affected than emerging economies in Asia and South America. We demonstrate that this heterogeneity in responses is not only attributable to differences in energy intensity in production across regions but also to degree of openness and the investment share in GDP.
hdl:11250/2496827
Keywords: C32; E32; F41; 330; FAVAR; factor augmented vector autoregressions; oil prices; emerging and developed countries; demand and supply shocks